Dark matter in a 'Z IND. 3'-symmetry extension of the Standard model - Koerich, Luan Vinícius [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Dark matter accounts for approximately 85% of all the matter in the universe. It is known to have a long lifetime, to be neutral and to interact with ordinary matter almost only gravitationally. There have been several models to suggest possible particles for the dark matter, many of them relying on extensions to the standard model of elementary particles. In particular, there are SIMP (strongly-interacting massive particles) models, which extend the standard model by an extra scalar sector containing the dark-matter particles, whose stability is provided by a discrete symmetry. This symmetry also extends the possible interactions between the dark-matter particles to beyond the usual pair annihilation and Lee-Weinberg scenario described by the WIMP (weakly-interacting massive particles) models. In our study, we postulate the existence of an extended dark sector with a 'Z IND. 3' discrete symmetry, which is the consequence of a global U(1)DM symmetry breaking. This symmetry allows the semi-annihilation and 3 'SETA' 2 annihilation processes to take place, besides the usual self-annihilation process. We will study each of these three scenarios, solving the respective Boltzmann equations and comparing the correspondent relic abundance to the observed one, in order to verify the liability of each of them. We will start by reviewing important aspects of standard cosmology and presenting our model. Then we will review the numerical solutions for the equations, and present our own results for semi-analytical solutions to the semi- and 3 'SETA' 2 annihilation processes. We will end by presenting our own results on solving the 3 'SETA' 2 Boltzmann equation for a temperature-dependent cross-section, calculated with the CalcHEP package

A matéria escura é responsável por cerca de 85% de toda a matéria do universo. Sabe-se que ela possui um longo tempo de vida, que é neutra e interage com a matéria comum apenas gravitacionalmente. Muitos modelos foram aventados para descrever as possíveis partículas de matéria escura, muitos deles baseados em extensões do modelo padrão para partículas elementares. Em particular, há os modelos de partículas massivas interativas por força forte, os SIMPs, que estendem o modelo padrão com um setor escalar extra contendo todas as partículas de matéria escura, cuja estabilidade é garantida por uma simetria discreta, a qual respeitam. Essa simetria também estende as possível interações entre as partículas de matéria escura para além da usual auto-aniquilação de pares e do contexto do problema de Lee-Weinberg, descrito pelas partículas massivas interagentes por força fraca, os WIMPs. Neste trabalho postulamos a existência de um setor escalar com uma simetria discreta 'Z IND. 3'; consequente de uma quebra de simetria U(1)DM global. Esta simetria permite que processos de semi-aniquilação e aniquilação 3 SETA 2 também ocorram, além do usual processo de auto-aniquilação. Estudaremos esses três cenários, encontrando as soluções das equações de Boltzmann e comparando suas respectivas abundâncias com o resultado observacional, para podermos avaliar nosso modelo. Começaremos por revisar importantes conceitos da cosmologia padrão e por apresentar o modelo. Então revisaremos as soluções numéricas para as equações, e apresentaremos nossos próprios resultados para soluções semi-analíticas dos processos de semianiquilação e de aniquilação 3 'SETA' 2. Concluiremos por apresentar nossos próprios resultados para a solução da equação de Boltzmann para o processo 3 'SETA' 2 usando uma seção de choque que é dependente da temperatura, calculada com o pacote CalcHEP
Keywords: Dark matter (Astronomy); Matéria escura (Astronomia)